Marginal Membawa Masyarakat Maurek Bawang - Yunus, Muhammad; Azwar, Welhendri; Jamil, Muhamad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The Maurek Bawang community in Nagari Aie Winter is in a peripheral position and has limited access to resources, opportunities and opportunities to improve their standard of living. This causes people to be trapped in a cycle of poverty. The research method used is a descriptive qualitative research method. The results found that the solution to overcome the marginalization that occurred was that the local government launched a comprehensive community empowerment program. This empowerment program covers various aspects, such as increasing agricultural productivity, opening market access, developing capacity and skills, strengthening local institutions, as well as partnerships with related institutions. Even though this program has shown positive results, such as increasing productivity and income, there are still challenges that must be faced, such as limited natural resources, inadequate infrastructure, limited access to capital and technology, as well as climate change and natural disasters. To overcome these challenges, close cooperation and collaboration is needed between the government, related institutions and society itself.